The Effect of Early Warning System (EWS) and Risk-Based Capital (RBC) On Profitability and Stock Price (Study on Insurance Companies on the Indonesia Stock Exchange) - ., Andriani (Journal of Ecohumanism, 2025)
Insurance is a form of community financial management that anticipates future risks. The growing number of insurance companies in Indonesia certainly provides ample opportunities for people to choose insurance products. Insurance companies must also pay attention to financial performance in carrying out their operational activities. Early Warning System (EWS) and Risk-Based Capital (RBC) values are ratios that describe the financial condition of insurance companies. Good financial performance will show that finances are in stable condition, including the acquisition of profitability. The study examines the effect of EWS and RBC values on profitability. In addition, related to financial performance will have an impact on stock prices. So, this study also examines the effect of EWS and RBC values on stock prices. This research uses a quantitative approach. Researchers conducted tests through the SPSS application and path analysis on path analysis. The sample in this study amounted to 11 insurance companies in the 2019-2023 financial period. The results showed that the EWS value had no significant effect on the profits of insurance companies listed on the Indonesia Stock Exchange (IDX). Then the RBC value also has no significant effect on the profits of insurance companies listed on the IDX. For other dependent variables, namely stock prices. Partially, the EWS value has a positive effect on the share price of insurance companies listed on the IDX. However, the RBC value does not affect the share price of insurance companies listed on the IDX. Profit variables have an influence on stock prices, the higher the profit followed by an increase in stock prices. However, earnings cannot mediate the effect of EWS value and RBC value on stock prices.